Factors Associated with Binge Drinking—Findings from 2019 Kansas Behavioral Risk Factor Surveillance System. Issue 1 (December 2022) - Lines, Shannon R.; Marroquin, Aliya; Corbett, Steve; Sergeant, Julie; Choi, Won; Faseru, Babalola
Background : In the U.S., excessive drinking accounts for one in 10 deaths among adults aged 20–64 years old. Binge drinking is a common form of excessive alcohol consumption that contributes to this chilling statistic. Binge drinking is defined as women consuming four or more drinks or men consuming five or more drinks within a 2-h time span. Examining existing data on risk factors for binge drinking can inform strategies to prevent this deadly practice. Methods : The 2019 Kansas Behavioral Risk Factor Surveillance System (BRFSS) dataset consists of data collected from 11, 368 non-institutionalized adults aged 18 years and older with landline or cell phones. The dependent variable in this study was binge drinking status. The independent variables included several sociodemographic variables and risk factors. Data were analyzed using descriptive statistics, bivariate analysis, single logistic regression, and multivariable logistic regression. Results : In the population, 1, 447 (17.4%) were reported to be binge drinkers. Significant factors associated with binge drinking in the final model included sex (aOR = 0.53 (0.45–0.63)), age (18–24 years old aOR = 8.77 (6.02–12.79); 25–34 years old aOR = 7.10 (5.35–9.42); 35–44 years old aOR = 6.23 (4.73–8.19); 45–54 years old aOR = 3.87 (2.92–5.14); and 55–64 years old aOR = 2.58 (1.96–3.38)), income (15, 000–24, 999 aOR = 1.00 (0.63–1.58); 25, 000–34, 999 aOR = 1.61 (1.04–2.50); 35, 000-49, 999 aOR = 1.69 (1.13–2.55); ≥50, 000 aOR = 1.97 (1.34–2.89)), smokeless tobacco use (aOR = 2.09 (1.55–2.82)), and smoking/e-cigarette use (Cigarette user only aOR = 2.11 (1.69–2.65); E-cigarette user only aOR = 2.67 (1.62–3.17); dual cigarette and e-cigarette user = 3.43 (2.21–5.33)). Conclusion : Developing interventions that take into account elevated risk for binge drinking amongst demographic characteristics (i.e., age, sex, income) and lifestyle factors (i.e., smokeless tobacco use, and smoking/e-cigarette use) is crucial to lowering morbidity and mortality related to this form of excessive alcohol consumption.